تقييم الخصائص البيدولوجية للترب الزراعية في القطاع السابع من حوض الفرات الأدنى- سورية - حايك, شريف; يزبك, ابراهيم (Latakia University Journal -Engineering Sciences Series, 2018)
يقع القطاع السابع على الضفة اليمنى لنهر الفرات عند مدينة البوكمال على الحدود السورية – العراقية، وتبلغ مساحته 18140 هكتاراً. تُستثمَر معظم أراضي القطاع بشكل كثيف جداً، وتعتمد الزراعات فيه على الري بوساطة شبكات الري التي تتألف من أقنية وخنادق ترابية، تُضخ المياه فيها بالمضخات المنتشرة على ضفاف الفرات. يهدف البحث إلى تقييم الخصائص البيدولوجية للتربة الزراعية باستخدام تجارب مخبرية وحقلية، ومن أهم الخصائص: سرعة التسرب، النفاذية، الكثافة الظاهرية، المسامية، السعة الحقلية المائية، الرطوبة الطبيعية (الهيغروسكوبية–حد الذبول)، وذلك للمساهمة في اختيار الطرائق المثلى لأعمال الري والصرف، ولإعادة استصلاح الأراضي التي تأثرت بالملوحة وخرجت من الاستثمار. تمتاز تربة القطاع بأنها غضارية ورملية غضارية ورملية ناعمة، نفاذيتها منخفضة، والسعة الحقلية المائية لها أيضاً منخفضة بسبب منشأها الرسوبي، والمسامية الكلية منخفضة في الآفاق تحت السطحية بسبب ارتصاصها، ويوجد علاقة بين الرطوبة الهيغروسكوبية للتربة والتركيب البنائي لها. يوصي البحث بزراعة محاصيل بقولية ذات أعماق جذور مختلفة كي تساعد على تحسين بناء التربة، وضرورة استخدام الري بالرذاذ للتحكم بكمية المياه وعمق الترطيب. Seventh sector is located on the right bank of the Euphrates River at the town of Abu- Kamal, the Syrian-Iraq border, and its square 18140 hectares. Invest most heavily sector too, where crops depend on irrigation, irrigation networks mediated consisting of earthen trenches, canals and to pump water by pumps on the banks of the Euphrates. Research aims to assess the pedelogical properties of agricultural soils by using laboratory and field tests: leaching speed, permeability, density, porosity, water field capacity, natural humidity (hygroscopic– wilt limit), so as to contribute in choosing optimal modalities for irrigation and drainage, and rehabilitation Land affected by salinity and exited the investment. The soils of the sector are clay, clayey sand, fine sand, and it has low permeability, low water field capacity because of sedimentary origin, and the total porosity is low in the upper part of subsurface soil because of its impaction. There is a relationship between hygroscopic moisture of soils and its structural composition. The search recommend to agriculture Fabaceae crops with different roots deep to help improve soil building, and need to use spray irrigation method to control the water quantity and wetting depth.